(untitled) (Journal of actual problems of jurisprudence, 2023)
This scientific article discusses the concept and types of mediation features of the implementation of mediation based on a commission agreement. During the development of a market economy in the Republic of Kazakhstan, there is a need for a comprehensive study of the Treaty of commission, an institution of civil law, and the application of its scientific achievements in newly adopted regulations. At the same time, compiling these laws requires scientific elaboration of norms, elimination of contradictions, and additions to the existing law. Scientific work expands knowledge regarding the solution and development of legal issues of the contract of assignment, which is one of the conditions for the provision of services among civil law contracts, and mediation. In the system of civil legal contracts of the Republic of Kazakhstan, the arrangement of the commission has its role and place as a civil legal contract providing services. In the scientific article, with an analysis of the legal status of the commission agent as an intermediary and intermediary arising based on the commission agreement, the subject of the commission obligation considers the legal basis for the provision of services. A study is carried out to analyze the practical issues arising concerning the commission agreement. The relations based on the commission agreement are changing compared to the existing commission relations in previous periods. Keywords: commission agreement, the consignment agreement, concept of mediation, parties to the commission agreement, сommission obligation.